Pyroptosis-Related Patterns Predict Tumor Immune Landscape and Immunotherapy Response in Bladder Cancer - Yan, Yilin; Cao, Xiangqian; Wang, Zeyi; Huang, Zhengnan; Cai, Jinming; Tang, Pengfei; Yang, Chenkai; Zhang, Fang; Xia, Shujie; Shen, Bing (Frontiers in Molecular Biosciences, 2022)
Background Bladder cancer (BC) is a leading cause of death from malignancy, with a significant heterogeneity in the immunotherapeutic responsiveness of advanced status. Pyroptosis, a newly discovered inflammatory programmed cell death, is confirmed to play an indispensable role in tumorigenesis and antitumor activity. However, the effect of pyroptosis on the tumor immune landscape remodeling and immunotherapy in BC remains elusive. Methods We comprehensively evaluated mRNA expression and genomic alterations of 33 pyroptosis-related genes (PRGs) in BC, and evaluated patterns of pyroptosis in publicly available BC datasets. An unsupervised clustering method was used to classified patients into distinct patterns. Then we established a pyroptosis related signature score (PS-score) model to quantify the pyroptosis-related patterns of individual BC patient using principal component analysis. Furthermore, we correlated the patterns with the immune landscape and response efficacy of immunotherapy. Results Two pyroptosis-related patterns were identified in BC, and distinct patterns showed various immune characteristics. Patterns with high expression level of PRGs exhibited a survival advantage and showed higher infiltration of cytotoxic lymphocytes. Tumors with low PS-score were characterized by elevated tumor-infiltrating lymphocytes and considered ‘hot’. Further analysis revealed that PS-score was an independent prognostic factor and could predict the response to immunotherapy for patients with advanced BC. We found a significant positive association between AHNAK2 expression and PS-score. Functional assays showed that AHNAK2 knockdown was correlated with attenuated invasive ability. Conclusions This work comprehensively demonstrated the potential function of pyroptosis-related patterns in bladder tumor immune landscape and identified their therapeutic liability in immunotherapy. Our study enhanced our understanding of immune landscape and provided a new approach towards more effective immunotherapy strategies.